2019
DOI: 10.1007/jhep01(2019)089
|View full text |Cite
|
Sign up to set email alerts
|

Comments on Lorentz transformations, dressed asymptotic states and Hawking radiation

Abstract: We consider two applications of the factorization of infrared dynamics in QED and gravity. The first is a redefinition of the Lorentz transformations that makes them commute with supertranslations. The other is the process of particle creation near a black hole horizon. For the latter we show that the emission of soft particles factors out of the Smatrix in the fixed-background approximation and to leading order in the soft limit. The factorization is implemented by dressing the incoming and outgoing asymptoti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(81 citation statements)
references
References 44 publications
6
72
3
Order By: Relevance
“…Our results bring further evidence that Hawking radiation is not modified by soft hair implanted by supertranslating shock waves, at least not using the mechanisms analyzed here. It complements the results of [56] obtained from the perspective of dressing states with infrared soft hair. While these results are consistent with the soft hair conjecture [47], they do not provide a mechanism for correlating in a bijection soft and hard sectors.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Our results bring further evidence that Hawking radiation is not modified by soft hair implanted by supertranslating shock waves, at least not using the mechanisms analyzed here. It complements the results of [56] obtained from the perspective of dressing states with infrared soft hair. While these results are consistent with the soft hair conjecture [47], they do not provide a mechanism for correlating in a bijection soft and hard sectors.…”
Section: Resultssupporting
confidence: 75%
“…Such displacement memory leads to a shift of the canonical variable defined at I + that encodes the displacement memory and that is also shifted by BMS supertranslations. We conclude that the limiting advanced time v 0 (θ, φ) is a functional of the leading order matter fields and directly relates to displacement memory at null infinity, consistently with the analysis of [29,56]. In that regard, the existence of a generalization of the limiting advanced time v 0 in any dimension is consistent with the existence of the triangular relationship between supertranslations, displacement memory and soft theorems in any dimension at null infinity [72][73][74].…”
Section: Comments On Hawking Radiationsupporting
confidence: 78%
“…Evidence that Hawking radiation is not modified by soft hair implanted by supertranslating shock waves comes from [86], at least using the mechanisms analyzed therein. Their results complement those of [87] obtained from the perspective of dressing states with soft hair where the authors showed that the spectrum of Hawking radiation (without backreaction) emitted in the Schwarzschild background is unchanged after including the dressing of asymptotic states with soft form factors. The relevance of soft hair to black hole entropy is still an open question.…”
Section: Discussionsupporting
confidence: 78%
“…If the coproduct was primitive the T T ot pq would be given purely by the eigenvalue T pq of the soft particle and likewise for the late quanta. This corresponds to the argument of [34][35][36][37], because the supertranslation charges conservation would constrain only soft particles. But in the case of κ-deformed BMS the total supertranslation charges of early and late quanta are also functions of the Poincaré momenta of the hard particles.…”
Section: Exchange Of Charge Between Soft and Hard Part During The Timmentioning
confidence: 97%
“…This argument was refuted in a series of papers [34], [35], [36], [37] where it is argued that soft hair could not resolve the black hole unitarity problem, because their time evolution is trivial and their conservation laws are automatically satisfied. The soft modes carrying them effectively decouple from the hard ones and moreover there is a canonical transformation which strips the hard modes from all the supertranslational charges.…”
Section: Exchange Of Charge Between Soft and Hard Part During The Timmentioning
confidence: 99%